2019
DOI: 10.1158/1535-7163.mct-18-1329
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminase Activity of L-Asparaginase Contributes to Durable Preclinical Activity against Acute Lymphoblastic Leukemia

Abstract: We and others have reported that the anticancer activity of L-asparaginase (ASNase) against asparagine synthetase (ASNS)-positive cell types requires ASNase glutaminase activity, whereas anticancer activity against ASNS-negative cell types does not. Here, we attempted to disentangle the relationship between asparagine metabolism, glutamine metabolism, and downstream pathways that modulate cell viability by testing the hypothesis that ASNase anticancer activity is based on asparagine depletion rather than gluta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 16 publications
(23 reference statements)
1
61
0
Order By: Relevance
“…l- asparaginases have variable amount of glutaminase activity as a secondary activity, and whether the glutaminase activity has any clinical relevance is debatable. 21 , 22 Recent studies by Parmentier et al 23 and Chan et al 24 have shown that glutaminase activity is required along with L-asparaginase activity for the effective management of ALL. Many of the toxic adverse effects of l- asparaginase therapy previously were attributed to the l- glutaminase activity.…”
Section: Discussionmentioning
confidence: 99%
“…l- asparaginases have variable amount of glutaminase activity as a secondary activity, and whether the glutaminase activity has any clinical relevance is debatable. 21 , 22 Recent studies by Parmentier et al 23 and Chan et al 24 have shown that glutaminase activity is required along with L-asparaginase activity for the effective management of ALL. Many of the toxic adverse effects of l- asparaginase therapy previously were attributed to the l- glutaminase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no attempt was made to correlate ASNS protein expression to enzymatic activity. However, more recent results from the same group, obtained with a murine leukemia model of ASNS-null ALL, indicate that, actually, glutaminase activity was needed for a durable suppression of the tumor (32). Further investigation is needed to fully understand the role of cellular Gln levels on ASNase sensitivity and glutaminase action in ALL progression.…”
Section: Low Asns Expression In Acute Lymphoblastic Leukemia: Old Obsmentioning
confidence: 99%
“…Nevertheless, despite all advances and a high rate of therapeutic success in ALL, several deficiencies of asparaginase therapy have been reported. A still debated question is whether substrate specificity, particularly the l -glutaminase activity, is required for clinical efficiency 10 , or it is mainly a contributor to side effects 11 13 .…”
Section: Introductionmentioning
confidence: 99%